Kekuatan Pembuktian Sertifikat Hak Milik atas Tanah sebagai Alat Bukti Kepemilikan yang Sah - Wibhawa, Felix Rocky; Dewi, Anak Agung Istri Ari Atu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The purpose of this paper is to find out the legality of the position of property rights certificates and the strength of proof of property rights certificates as legal evidence of ownership in Indonesia. This paper uses the normative legal method. This study uses a legal and conceptual approach. The results of the study indicate that the certificate of ownership has a legal status because it is explicitly and explicitly regulated in the laws and regulations. The certificate of ownership has strong evidentiary power but is not absolute. The title certificate will become absolute if it has fulfilled the criteria stipulated in Article 32 paragraph (2) of the PP on Land Registration, namely legally issued, in good faith and in real control for more than 5 years.